Two new synonyms among Panchaetothripinae (Thysanoptera: Thripidae) with three species newly recorded from China - Wang, Zhaohong; Mound, Laurence; Mao, Runqian; Tong, Xiaoli (Zootaxa, 2022)
Helionothrips mube and Panchaetothrips bifurcus are here recognized as new synonyms of Helionothrips aino and Panchaetothrips timonii based on large numbers of specimens and continuous morphological differences. Three species, Caliothrips insularis, Hercinothrips femoralis and Phibalothrips rugosus are newly recorded from China and the previous record of Caliothrips indicus from China is here considered incorrect. Illustrations of males and larvae of Hercinothrips femoralis are also provided.